2011
DOI: 10.1161/strokeaha.110.602276
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Inflation Times During Balloon-Assisted Aneurysm Coil Embolization and Ischemic Complications

Abstract: Background and Purpose-The introduction of balloon remodeling has revolutionized the approach to coiling of wide-neck aneurysms. We studied the effects of balloon inflation during coil embolization on ischemic complications. Methods-A retrospective review was undertaken of the most recent 147 patients undergoing balloon remodeling for unruptured intracranial aneurysm coil embolization at a single institution (81 balloon, 66 unassisted). All underwent postprocedural MRI. Results-Among patients in the "balloon" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 11 publications
2
48
1
Order By: Relevance
“…The use of balloon may increase the incidence of ischemic affairs (15). But in our group, no balloon related complication…”
Section: Discussioncontrasting
confidence: 48%
“…The use of balloon may increase the incidence of ischemic affairs (15). But in our group, no balloon related complication…”
Section: Discussioncontrasting
confidence: 48%
“…Because of high blood rates of fistulas, even in total arterial steal, the damaged side of the cerebral hemisphere is in a state of relative hypoperfusion. Pre-and postoperative MR imaging should have been performed to identify asymptomatic cerebral infarction related to nondetachable balloons and flaking of solidified Onyx around the ostium, even though there is no significant relationship between balloon inflation practices and ischemic events, as reported by Spiotta et al, 27 and no new ischemic events were observed in any of these 23 patients either. Besides, long-term follow-up and larger case series are needed for further evaluation of the safety and efficacy of Onyx for the transarterial balloon-assisted embolization for TOCFs.…”
Section: Discussionmentioning
confidence: 86%
“…The advent of self-expanding neurovascular stents and continued advances in endovascular techniques, such as balloon remodeling, [15][16][17] single stent reconstruction, 4,18 and transcirculation techniques 8 have greatly improved the ability to treat intracranial aneurysms. However, achieving an uncomplicated and complete obliteration of complex bifurcation aneu- rysms remains technically challenging.…”
Section: Discussionmentioning
confidence: 99%